Analyzing the landscape characteristics promoting the establishment and spread of gorse (Ulex europaeus) along roadsides - R. León Cordero (Ecosphere, 2016)
Abstract The International Union for Conservation of Nature listed gorse (Ulex europaeus, Fabaceae), a heliophilous evergreen shrub, as one of the world's 100 worst invasive species. Over the years, multiple attempts have been made for controlling gorse, including biological methods, but they have not been fully successful. This study aims to investigate some aspects that still remain unexplored such as the relationship between anthropogenic disturbances with the spatial mechanisms of species spread. We aimed to fill this gap by analyzing the role of transportation network configurations and landscape context on gorse propagation. We surveyed the presence of gorse in southern Brazilian forest‐grassland mosaics by completing landscape‐level road transects coupled with remote sensing, to evaluate land use and landscape structure. A binary logistic regression model was performed to test the influence of independent variables (e.g., road orientation, type and category in addition to distance to the nearest habitat patch of forest, grassland and anthropogenic area) on gorse occurrence. Our results showed that the structure of road networks can facilitate the spread of heliophilous taxa like gorse. Specifically, local, paved, NWSE and NS‐oriented (which exhibited high light exposure) roads had the highest probability of finding gorse. This suggests that human transportation activity (traffic, road construction, and maintenance) constitutes a significant dispersal agent for the species. In addition, the landscape matrix context also played a significant role; gorse was most prevalent along roadsides close to urban or agricultural areas than to forests and grasslands. No area was completely free from disturbances, such as fire, livestock grazing, and silviculture, in these seminatural landscapes. We concluded that, disturbances affecting small‐scale processes, at roadside and adjacent habitat patches, were probably as important factors explaining gorse occurrence as the urban impact. Furthermore, the current work also emphasizes the need of understanding the complexity of interacting factors. Our work has important implications for ecosystem conservation and habitat management, and consequently should be considered a prior step in establishing new approaches for gorse control.